Preparation of Chlorodeoxycellulose from Shambat Cotton Lint Using Dimethyl Acetamide / Lithium Chloride Solvent System - A. M. Salim, Inaam; A. Ragab, Yousif (Gezira Journal of Engineering and Applied Sciences, 2018)
Cotton cellulose has interesting properties which can be controlled to a large degree by chemical modification. This study was designed to prepare cellulose derivatives with different functional groups using novel homogenous solubilisation media. Raw cotton was modified (mercerized) in (15%) NaOH solution to weaken the aggregation of the bundles of cotton cellulose fibers and; subsequently, to facilitate the dissolution in N,N-dimethylacetamide/lithium chloride (DMA/LiCl) solvent system. Chlorodeoxycellulose was synthesized by treatment of the solubilised cotton cellulose with N-chlorosuccinimide in the presence of triphenylphosphine to convert the hydroxyl groups into the chlorodeoxy derivative of cellulose. The chemical structure of this derivative was investigated using infrared spectroscopy, elemental analysis and thermal analysis (TGA, DSC). Chlorordeoxycellulose  proved to be a flame retardant polymer; since  thermal analysis showed that it has less thermal stability compared to unmodified cellulose. Thermal analysis also showed different behaviour between modified and unmodified cotton cellulose. Solubility in some organic solvents was tested for the prepared derivative to explore possible new uses and applications. This research has shown the versatility of Shambat cotton cellulose as a raw material for novel and advanced cellulose-based materials; and to widen and simplify the existing synthetic methodologies for cellulose modification, to yield novel derivatives using homogenous reaction media.